Pharmacokinetics and Safety of Clofazimine in Children With Rifampicin-Resistant Tuberculosis - Hughes, Jennifer A; Solans, Belén P; Garcia-Prats, Anthony J; Draper, Heather R; Schaaf, H Simon; Nielsen, James C; Nortier, Elri; Courtney, Ingrid; Palmer, Megan; van der Laan, Louvina; Savic, Radojka M; Hesseling, Anneke C (The Journal of infectious diseases, 2025)
Abstract Background We described the pharmacokinetics and safety of clofazimine in children treated for multidrug/rifampicin-resistant tuberculosis (MDR/RR-TB). Methods Children aged <18 years were eligible. Clofazimine was administered by weight-based dosing. Sparse and semi-intensive pharmacokinetic sampling was completed at baseline and weeks 2 and 16. Clofazimine weekly area under the concentration time-curve (wAUC) was compared with the target wAUC (60.87 mg × h/L and 111.79 mg × h/L) in adults receiving clofazimine (100 mg) daily for MDR/RR-TB and leprosy, respectively. Safety monitoring included measurement of QT interval prolongation and laboratory assessment. Results Twenty children were included: median age was 6.0 years (IQR, 1.6–14.4); 6 (30%) were male. Median clofazimine wAUC was 162.94 (IQR, 130.06–263.95), >25% higher than the target adult wAUC in adults with MDR/RR-TB (111.79; IQR, 81.9–151.9). No serious or grade ≥3 cardiac events occurred. There was a QT interval increase of 0.02 milliseconds for every 1-µg/L increase in clofazimine concentration. One severe adverse event (elevated alanine transferase) led to temporary withdrawal of clofazimine. Conclusions The clofazimine doses used achieved substantially higher exposures in children than adults receiving standard clofazimine doses. The association of higher clofazimine exposures and QT interval prolongation may pose unnecessary risk to children, particularly in combination with other QT-prolonging drugs. Clinical Trials Registration South African National Clinical Trials Register (https://sanctr.samrc.ac.za/; DOH-27-0620-6415). We investigated the pharmacokinetics and safety of clofazimine in children routinely treated for rifampicin-resistant tuberculosis. Semi-intensive and sparse sampling was completed. Clofazimine exposures were considerably higher than protocol-specified adult targets, with a linear relationship observed between clofazimine concentrations and increasing QT interval.